Indeterminacy with inflation-forecast-based rules in a two-bloc model - Nicoletta Batini; Paul Levine; Joseph G. Pearlman (European Central Bank (ECB), 2004)
We examine the performance of forward-looking inflation-forecast-based rules in open economies. In a New Keynesian two-bloc model, a methodology first employed by Batini and Pearlman (2002) is used to obtain analytically the feedback parameters/horizon pairs associated with unique and stable equilibria. Three key findings emerge: first, indeterminacy occurs for any value of the feedback parameter on inflation if the forecast horizon lies too far into the future. Second, the problem of indeterminacy is intrinsically more serious in the open economy. Third, the problem is compounded further in the open economy when central banks respond to expected consumer, rather than pro- ducer price inflation.
Keywords: E52; E37; E58; 330; in°ation-forecast-based rules; indeterminacy; open economy; Taylor rules